Current Trends in Atherogenesis - Rezzani, Rita (IntechOpen, 2013)
This book collects the state of the art of the antioxidants from the clinical and experimental approaches in order to bring a better understanding of the mechanisms and useful therapies for these diseases. We hope that it can indicate new "current trends" for identifying new aspects regarding this scientific problem involving not only anatomical and functional, but also clinical questions.